Efektivitas Pelaksanaan Online Single Submission (OSS) Untuk Pendaftaran Badan Hukum Perseroan Terbatas (PT) Oleh Notaris - Hutama, Yonanda Gumilang; Supriyono (Indonesian Journal of Law and Justice, 2024)
Commercial or operational business licenses are issued by the OSS Institution for and on behalf of Ministers, Institutional Leaders, Governors, or Regents and Mayors after the business actor obtains a business license and to carry out commercial or operational activities by fulfilling the requirements or commitments.  The OSS institution is responsible for issuing Business Identification Numbers (NIB), location permits, and business licenses. Basically, this regulation aims to cut the process of issuing business licenses which has been convoluted. The purpose of this study is to find out: 1) how to make a Limited Liability Company Deed. 2) the effectiveness of business license registration through the Online Single Submission (OSS) system for the registration of a Limited Liability Company (PT) Legal Entity by a Notary as a means of One-Stop Integrated Licensing Services (PPTSP). 3) obstacles and solutions faced in using the Online Single Submission (OSS) system for the registration of a Limited Liability Company (PT) Legal Entity. 4) example of a Deed of Incorporation of a Limited Liability Company. The approach method used in this study is sociological juridical, namely legal research that is carried out on the real state of society or the community environment with the intention and purpose of finding facts (fact-finding) and then identifying (problem-identification) and ultimately leading to problem solving (problem-solution). The results of the study are: 1) the establishment of a Limited Liability Company cannot be separated from the role of a Notary, as stipulated in Article 7 paragraph (1) above that the establishment of a Limited Liability Company must be with a Notary deed. From the beginning when the founders of a Limited Liability Company face the Notary, from that moment on, the Notary is responsible for carrying out what is requested and ordered by law. 2) The effectiveness of business license registration through the Online Single Submission (OSS) system for the registration of a Limited Liability Company (PT) Legal Entity by a Notary as a means of One-Stop Integrated Licensing Services (PPTSP) in the Wonosobo Regency area is still not effective because the implementation of OSS from the beginning of the issuance of Government Regulation No. 24 of 2018 concerning Electronically Integrated Business Licensing Services in the first year for the management of legal entities still poses problems.  3) The obstacles faced include that the system still tends to be weak. The OSS system does not carry out the entire licensing process. Many of the business actors who establish limited liability companies (PTs) still need the help of consultants to fill out the forms in the OSS system. 4) the establishment of a Limited Liability Company through the mechanism of the legal entity administration system begins with the implementation of an application for the reservation of the company's name and is followed up with the preparation of a Notary Deed of Incorporation of the Limited Liability Company.